Analisis Kualitas Mikrobiologi Air Minum Isi Ulang di Depo Air Minum Isi Ulang Kelurahan Jemur Wonosari Kota Surabaya - Ajeng Dwi Rahmawati; Akas Yekti Pulih Asih; Edza Aria Wikurendra (Universitas Widya Gama Mahakam Samarinda, 2021)
Background: Based on the preliminary test using laboratory tests from three refill drinking water samples in Jemur Wonosari Village, all three were positive for Coliform. Therefore, researchers are interested in researching Analysis of the Microbiological Quality of Refilled Drinking Water at the Refill Drinking Water Depot in Jemur Wonosari Village. Objectives: Knowing the microbiological quality of refill drinking water produced at the refill drinking water depot in Jemur Wonosari Village. Research Methods: This research is a descriptive study with a cross-sectional quantitative approach using primary and secondary data sources. The population in this study were all 13 refill drinking water depots. The research takes the total population. Refillable drinking water samples were tested at the Gayung Sari Regional Health Service Laboratory. Data analysis used descriptive analysis by comparing the results of laboratory tests with Permenkes 492 of 2010. Results: The results showed that 13 samples found that 13 samples were positive for Coliform, and 13 samples were negative for Escherichia coli. According to Permenkes No. 429 of 2010, the maximum limit per 100 ml of sample is 0. So the 13 samples of refill drinking water based on microbiological parameters, namely Escherichia coli in refilled drinking water, meet the standard while the Coliform does not meet the standard. Conclusion: All refill drinking water depots in Keluraham Jemur Wonosari produce refilled drinking water whose quality does not meet the government's microbiological standards. There is a need for increased supervision and guidance at refill drinking water depots.